The Case of Roshonara Choudhry: Implications for Theory on Online Radicalization, ISIS Women, and the Gendered Jihad - Elizabeth Pearson (Policy & Internet, 2016)
As dozens of British women and girls travel to join Islamic State in Syria and Iraq, there are increasing concerns over female radicalization online. These fears are heightened by the case of Roshonara Choudhry, the first and only British woman convicted of a violent Islamist attack. The university student in 2010 stabbed her Member of Parliament, after watching YouTube videos of the radical cleric Anwar Al Awlaki. Current radicalization theories portray Choudhry as a “pure lone wolf,” a victim of Internet indoctrination, without agency. This article explores how gender factors in her radicalization, to present an alternative to existing theoretical explanations. An engagement with gender reveals its role in Choudhry's radicalization, first, in precluding her from a real‐world engagement with Islamism on her terms, pushing her to the Internet; then in increasing her susceptibility to online extremist messages; finally, in fomenting an eventually intolerable dissonance between her online and multiple “real” gendered identities, resulting in violence. The article emphasizes the transgressive nature of this act of female violence in Salafi‐Jihadi ideology; also, the importance of this gendered ideology as the foundation of ISIS recruitment online. It emphasizes the importance of understanding the operation of gender in the Jihad's production of violence, and roles for men and women alike.